THE STUDY OF SCHOOLING: FIELD BASED METHODOLOGIES IN EDUCATI0NAL RESEARCH AND EVALUATION (Authors: Thomas Popkewitz and Robert Tabachnick) - Van Fleet, Alason (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1982)
Thomas Popkewitz and Robert Tabachnick. THE STUDY OF SCHOOLING: FIELD BASED METHODOLOGIES IN EDUCATI0NAL RESEARCH AND EVALUATION. New York, N.Y.: Praeger Publishers, 1981. 301 pp. 34.60.